Final answer:
By using the trapezium area formula, we established that the area in terms of x is (x+4)(x-5), which simplifies to x^2 - x - 20. Setting this equal to the given area of 36 cm^2 and rearranging, we derive the equation x^2 - x - 56 = 0.
Step-by-step explanation:
To demonstrate that x2 - x - 56 = 0, we must use the properties of a trapezium and the given area. The area A of a trapezium can be calculated with the formula A = \((a+b)/2\) * h, where a and b are the lengths of the parallel sides and h is the height. In this case, one pair of parallel sides is x+2 and x+6, and the area is given as 36 cm2. If we let the height h of the trapezium be x - 5, then the area is:
A = \((x+2+x+6)/2\) * (x-5)
36 = \((2x+8)/2\) * (x-5)
36 = (x+4)(x-5)
36 = x2 - 5x + 4x - 20
36 = x2 - x - 20
Adding 20 to both sides:
56 = x2 - x
Therefore, the equation becomes:
x2 - x - 56 = 0
This matches the equation we needed to show, thus completing the proof.